The Relationship Between Halal Tourism Development And Regional Original Income in Indonesia - Fariana, Andi; Nur Aisyah, Alifia; S, Saripudin (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2022)
This study aimed to determine the relationship between the financial performance of local revenue and the halal tourism sector in DKI Jakarta. This qualitative descriptive research analyzes the information obtained from the results of a study that has been carried out before and then is complemented by interviews with several competent parties. Then a literature review is carried out on various published texts such as local government reports, regional regulations, and other information. from government websites. Based on the search, it was found that there were strategic steps in developing halal tourism in DKI Jakarta, including concrete Implementation in the form of preparing various supporting facilities as well as various forms of innovation and sharia services in banking in the form of sharia schemes to support the multiple needs of halal tourism actors such as JakQR, JakOne to later JakCard. It was also found that there is quite a large amount of income for regional original income from the tourism sector in DKI Jakarta, but the percentage that comes from halal tourism has yet to be identified. The recommendation from this research is to stay focused on developing the potential of halal tourism in DKI Jakarta and the need to issue Regional Regulations immediately.